Totally-closed connecting paint for ship body below ship waterline and preparation method of totally-closed connecting paint

By using specific components and processes in ship coatings, the shortcomings of existing coatings in anti-corrosion and environmental protection are solved, and efficient and environmentally friendly hull anti-corrosion effects are achieved, reducing maintenance costs and environmental impacts.

CN119823618APending Publication Date: 2025-04-15CHENGCANG YIJIA ENVIRONMENTAL PROTECTION TECHNOLOGY (FUJIAN) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411898790.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing marine coatings have problems such as insufficient environmental protection performance, poor anti-corrosion effect, frequent maintenance, and increased economic costs and environmental burden in terms of corrosion protection.

Method used

Provide a fully enclosed joint paint of hull below the ship waterline, which consists of glass fiber, hydroxyethyl cellulose ether, propylene glycol, n-butanol, m-xylene, titanium dioxide, iron oxide red, silicone resin emulsion, ordinary emulsion, polydimethylsiloxane, thickener and defoaming agent, and ensures the efficient anticorrosion and environmental protection performance of the coating through specific mixing ratios and process steps.

Benefits of technology

This coating can effectively seal the isolation between the hull and the external medium, improve the physical performance of the coating, reduce the cost and maintenance frequency of ships, reduce the potential impact on the marine ecosystem, and extend the service life of the hull.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823618A_ABST
    Figure CN119823618A_ABST
Patent Text Reader

Abstract

The invention provides totally-closed connecting paint for a ship body below a ship waterline and a preparation method of the totally-closed connecting paint. The method comprises the following steps: A1, mixing glass fibers and a base material; a2, hydroxyethyl cellulose ether, propylene glycol, n-butyl alcohol and m-xylene are added; a3, adding titanium dioxide and iron oxide red; a4, adding the silicon resin emulsion and the common emulsion; a5, adding the polydimethylsiloxane and the thickening agent; and A6, finally adding the defoaming agent. And each step has a specific proportion and a specific mixing condition, so that the quality and the performance of the coating are ensured. The totally-closed connecting paint can reduce chemical corrosion and electrochemical corrosion of a ship body and prolong the service life of a ship.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of marine engineering and coating technology, and more specifically to a fully enclosed joint paint for a hull below a ship's waterline and a preparation method thereof. Background Art

[0002] In the existing ship coating technology, the main function of the coating is to protect the hull from corrosion and electrochemical corrosion, but the main components of these coatings are epoxy resins and other components, which have limited sealing performance and material mechanical properties between the hull and the external medium, and are prone to partial or local corrosion or electrochemical corrosion between the hull and the medium, affecting the hull strength and even the service life of the ship. From a technical principle, the adhesion and material mechanical properties of this fully enclosed joint paint to the hull are more suitable for the underwater part of the ship. The anti-corrosion ability can reach 10 years, and the efficiency may be reduced due to environmental changes.

[0003] In the process of implementing the embodiments of the present invention, the inventors found that there are at least the following problems or defects in the prior art: first, the environmental performance of the coating is insufficient, and the harmful substances contained in it pose a threat to the marine environment; second, the anti-corrosion effect of the coating is not ideal, and frequent maintenance is required, which increases economic costs and environmental burdens; third, the durability and stability of the coating need to be improved to adapt to the changing marine environmental conditions. Summary of the invention

[0004] The invention provides a fully enclosed joint paint for a ship's hull below the waterline and a preparation method thereof.

[0005] In a first aspect of the present invention, a fully enclosed joint paint for a hull below the waterline of a ship is provided, wherein the paint is composed of the following components by mass percentage: 30%-50% glass fiber, 1%-3% hydroxyethyl cellulose ether, 2%-5% propylene glycol, 3%-6% n-butanol, 4%-8% m-xylene, 5%-15% titanium dioxide, 1%-5% red iron oxide, 6%-12% silicone resin emulsion, 7%-13% ordinary emulsion, 0.5%-2% polydimethylsiloxane, 0.3%-1.5% thickener, 0.1%-0.5% defoamer, and the rest is a base material.

[0006] Furthermore, the mass content of glass fiber in the coating is 35%-45%, the mass content of hydroxyethyl cellulose ether is 2%-4%, the mass content of propylene glycol is 3%-5%, the mass content of n-butanol is 4%-6%, and the mass content of m-xylene is 5%-7%.

[0007] In a second aspect of the present invention, a method for preparing a fully enclosed joint paint for a ship below the waterline is provided, which specifically comprises the following steps:

[0008] Step A1: mixing glass fiber with a base material to form a glass fiber base material, wherein the mixing ratio of the glass fiber to the base material is 30%-50%;

[0009] Step A2: adding hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene to the glass fiber base material and mixing them evenly, wherein the added amounts of hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene account for 1%-3%, 2%-5%, 3%-6% and 4%-8% of the total mass of the coating, respectively;

[0010] Step A3: adding titanium dioxide and red iron oxide to adjust the color and physical properties of the coating, wherein the amounts of titanium dioxide and red iron oxide added account for 5%-15% and 1%-5% of the total mass of the coating, respectively;

[0011] Step A4: adding silicone resin emulsion and common emulsion to increase the stability and functionality of the coating, the added amounts of silicone resin emulsion and common emulsion account for 6%-12% and 7%-13% of the total mass of the coating respectively;

[0012] Step A5: adding polydimethylsiloxane and thickener to improve the film-forming property and workability of the coating, wherein the amount of polydimethylsiloxane and thickener added is 0.5%-2% and 0.3%-1.5% of the total mass of the coating, respectively;

[0013] Step A6: Finally, add the defoamer and mix well to obtain the final coating product. The amount of the defoamer added accounts for 0.1%-0.5% of the total mass of the coating.

[0014] Furthermore, in the step A1, the mixing time of the glass fiber and the base material is controlled to be between 30 minutes and 1 hour, and the mixing speed is between 200 and 300 revolutions per minute.

[0015] Furthermore, in step A2, the addition and mixing of hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene are carried out at room temperature, the mixing time is 20-40 minutes, and the mixing speed is 300-500 rpm.

[0016] Furthermore, in step A3, the dispersion of titanium dioxide and red iron oxide is carried out in a high-speed stirrer at a stirring speed of 400-600 rpm and a stirring time of 40-60 minutes.

[0017] Furthermore, in step A4, the silicone resin emulsion and the common emulsion are mixed by low-speed stirring, the stirring speed is 100-200 rpm, and the stirring time is 15-30 minutes.

[0018] Furthermore, in step A5, the addition of polydimethylsiloxane and thickener is carried out when the coating temperature is controlled at 25° C.-35° C., the mixing speed is 200-300 rpm, and the mixing time is 20-40 minutes.

[0019] Furthermore, in step A6, the defoaming agent is added after the coating has completed preliminary curing, the mixing speed is 50-100 rpm, and the mixing time is 10-20 minutes.

[0020] Furthermore, during the preparation of the coating, quality inspection is carried out after each mixing step to ensure that the quality and proportion of each component meet the requirements. The final product must pass performance tests, including corrosion resistance tests, adhesion tests and weather resistance tests, to ensure that the performance of the coating meets the requirements of ship anti-fouling and drag reduction.

[0021] According to the above-mentioned embodiments of the present invention, at least the following beneficial effects are achieved: the fully enclosed joint paint for the ship hull below the waterline provided by the present invention can effectively isolate the hull from the external medium of the hull, and through its special formula and preparation process, effectively ensure the physical properties of the paint, and reduce the maintenance cost and maintenance frequency of the ship. The paint does not contain substances harmful to the environment, which reduces the potential impact on the marine ecosystem and meets modern environmental protection requirements. In addition, the preparation process of the paint is finely controlled to ensure the quality and performance of the paint, improve the corrosion resistance, adhesion and weather resistance of the paint, thereby extending the service life of the paint and reducing the frequency of maintenance and replacement.

[0022] By precisely controlling the addition ratio and mixing conditions of each component in the coating, the coating of the present invention can provide better physical properties and color adjustment, and enhance the stability and functionality of the coating. The film-forming properties and workability of the coating can be improved, making the coating more convenient and efficient in practical applications. The final product undergoes rigorous performance testing to ensure that the performance of the coating meets the requirements of physical isolation of the underwater part of the ship, providing an environmentally friendly, efficient and long-lasting protection solution for the ship. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The above and other objects, features and advantages of the exemplary embodiments of the present invention will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present invention are shown in an exemplary and non-limiting manner, in which:

[0024] Figure 1 A schematic flow chart of a method for preparing a fully enclosed joint paint for a ship's hull below the waterline provided by one embodiment of the present invention. DETAILED DESCRIPTION

[0025] The principles and spirit of the present invention will be described below with reference to several exemplary embodiments. It should be understood that these embodiments are provided only to enable those skilled in the art to better understand and implement the present invention, and are not intended to limit the scope of the present invention in any way. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0026] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. All features disclosed in this specification, or steps in all methods or processes disclosed, except for mutually exclusive characteristics and / or steps, can be combined in any way, unless otherwise described, and can be replaced by other equivalent or alternative features with similar purposes, that is, unless otherwise described, each feature is only one embodiment in a series of equivalent or similar features.

[0027] In some embodiments, a fully enclosed joint paint for a ship's hull below the waterline is composed of the following components by mass percentage:

[0028] Glass fiber 30%-50%, hydroxyethyl cellulose ether 1%-3%, propylene glycol 2%-5%, n-butanol 3%-6%, m-xylene 4%-8%, titanium dioxide 5%-15%, red iron oxide 1%-5%, silicone resin emulsion 6%-12%, ordinary emulsion 7%-13%, polydimethylsiloxane 0.5%-2%, thickener 0.3%-1.5%, defoamer 0.1%-0.5%, and the rest are base materials.

[0029] In this embodiment, a fully enclosed joint paint for a ship below the waterline is prepared, and its component ratio is clearly as follows, in mass percentage:

[0030] Glass fiber: 30% to 50% of the total mass, used as a reinforcing material to improve the mechanical strength of the coating;

[0031] Hydroxyethyl cellulose ether: 1% to 3% of the total mass, used as a thickener to adjust the viscosity of the coating;

[0032] Propylene glycol: 2% to 5% of the total mass, together with n-butanol (3% to 6% of the total mass) as a solvent to promote the dissolution of other components;

[0033] Meta-xylene: 4% to 8% of the total mass, used as a diluent to reduce the viscosity of the coating;

[0034] Titanium dioxide: 5% to 15% of the total mass, used together with red iron oxide (1% to 5% of the total mass) as a pigment to adjust the color of the coating;

[0035] Silicone resin emulsion: accounting for 6% to 12% of the total mass, together with ordinary emulsion (accounting for 7% to 13% of the total mass) as a film-forming substance, it helps to form a uniform coating film;

[0036] Polydimethylsiloxane: 0.5% to 2% of the total mass, specifically polydimethylsiloxane, used to improve the film-forming properties of the coating;

[0037] Thickener: 0.3% to 1.5% of the total mass, used to further adjust the rheology of the coating;

[0038] Defoamer: 0.1% to 0.5% of the total mass, used to reduce bubbles in the coating and ensure uniformity of the coating film;

[0039] The rest is the base material, which constitutes the main body of the paint.

[0040] The mass percentage range of each component in the coating is determined according to the specific application needs and performance requirements of the coating to achieve the best performance of the coating. Specifically, the content of glass fiber ranges from 35% to 45%, the content of hydroxyethyl cellulose ether ranges from 2% to 4%, the content of propylene glycol ranges from 3% to 5%, the content of n-butanol ranges from 4% to 6%, and the content of meta-xylene ranges from 5% to 7%. These proportions can ensure that the coating has good anti-fouling and drag-reducing properties while maintaining environmental protection characteristics.

[0041] In the specific preparation process of the coating, the content of the above components can be appropriately adjusted according to different application environments and performance requirements. For example, in order to improve the adhesion of the coating, the content of hydroxyethyl cellulose ether can be appropriately increased to the upper limit of its content range. Similarly, in order to reduce the drying time of the coating, the content of n-butanol can be appropriately reduced. In addition, alternative solvents or diluents can also be considered to adapt to specific environmental requirements or cost-effectiveness considerations while keeping the basic properties of the coating unchanged. All these adjustments should be made under the premise of ensuring that the overall performance of the coating meets the design standards.

[0042] In some embodiments, the mass content of glass fiber in the coating is 35%-45%, the mass content of hydroxyethyl cellulose ether is 2%-4%, the mass content of propylene glycol is 3%-5%, the mass content of n-butanol is 4%-6%, and the mass content of m-xylene is 5%-7%.

[0043] Preferably, during the specific preparation process of the coating, the contents of the above components can be fine-tuned to adapt to different application environments and performance requirements. For example, if the adhesion of the coating needs to be improved, the content of hydroxyethyl cellulose ether can be appropriately increased to close to the upper limit. Similarly, if the drying time of the coating needs to be reduced, the content of n-butanol can be appropriately reduced.

[0044] Furthermore, alternative solvents or diluents can be considered to meet specific environmental requirements or cost-effectiveness considerations while maintaining the basic performance of the coating. These adjustments need to be made under the premise of ensuring that the overall performance of the coating meets the design standards.

[0045] In some embodiments, the preparation method of the ship's hull fully enclosed joint paint below the waterline is as follows: Figure 1 As shown, the following steps are included:

[0046] Step A1: mixing glass fiber with a base material to form a glass fiber base material, wherein the mixing ratio of the glass fiber to the base material is 30%-50%;

[0047] Step A2: adding hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene to the glass fiber base material and mixing them evenly, wherein the added amounts of hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene account for 1%-3%, 2%-5%, 3%-6% and 4%-8% of the total mass of the coating, respectively;

[0048] Step A3: adding titanium dioxide and red iron oxide to adjust the color and physical properties of the coating, wherein the amounts of titanium dioxide and red iron oxide added account for 5%-15% and 1%-5% of the total mass of the coating, respectively;

[0049] Step A4: adding silicone resin emulsion and common emulsion to increase the stability and functionality of the coating, the added amounts of silicone resin emulsion and common emulsion account for 6%-12% and 7%-13% of the total mass of the coating respectively;

[0050] Step A5: adding polydimethylsiloxane and thickener to improve the film-forming property and workability of the coating, wherein the amount of polydimethylsiloxane and thickener added is 0.5%-2% and 0.3%-1.5% of the total mass of the coating, respectively;

[0051] Step A6: Finally, add the defoamer and mix well to obtain the final coating product. The amount of the defoamer added accounts for 0.1%-0.5% of the total mass of the coating.

[0052] It should be noted that this embodiment describes in detail a method for preparing a fully enclosed joint paint for a ship's hull below the waterline, which includes a series of specific steps to ensure uniform mixing and optimal performance of the paint. These steps involve adding different components to the base material in a specific proportion and order, and controlling the mixing time and speed at each stage to ensure uniformity and stability of the paint. The base material is the basic component of the paint, usually including resin and solvent, which constitute the main body of the paint.

[0053] Specifically, the steps of the preparation method are as follows: first, glass fiber is mixed with a base material to form a glass fiber base material, and the mixing ratio of glass fiber to base material is 30%-50%. Next, hydroxyethyl cellulose ether, propylene glycol, n-butanol and meta-xylene are added to the glass fiber base material, and the addition amounts of these components account for 1%-3%, 2%-5%, 3%-6% and 4%-8% of the total mass of the coating, respectively. Then, titanium dioxide and red iron oxide are added to adjust the color and physical properties of the coating, and their addition amounts account for 5%-15% and 1%-5% of the total mass of the coating, respectively. After that, silicone resin emulsion and ordinary emulsion are added to increase the stability and functionality of the coating, and their addition amounts account for 6%-12% and 7%-13% of the total mass of the coating, respectively. Next, polydimethylsiloxane and thickener are added to improve the film-forming performance and workability of the coating, and their addition amounts account for 0.5%-2% and 0.3%-1.5% of the total mass of the coating, respectively. Finally, add a defoamer, mix evenly to obtain a final coating product, and the amount of the defoamer added accounts for 0.1%-0.5% of the total mass of the coating.

[0054] Preferably, some operating parameters in the above steps can be refined or alternatives can be provided. For example, in step A1, the time for glass fiber to be mixed with base material can be controlled at 30 minutes to 1 hour, and the mixing speed is 200-300 rev / min, to ensure that glass fiber is evenly dispersed in base material. In step A2, the addition and mixing of hydroxyethyl cellulose ether, propylene glycol, n-butanol and meta-xylene can be carried out at room temperature, and the mixing time is 20-40 minutes, and the mixing speed is 300-500 rev / min, to ensure that these components are fully dissolved and mixed. For step A6, the addition of defoamer can be carried out after the coating completes preliminary curing, and the mixing speed is 50-100 rev / min, and the mixing time is 10-20 minutes, to ensure that the defoamer is evenly distributed and does not affect the curing process of the coating. The adjustment of these parameters can be optimized according to actual production conditions and equipment capabilities to achieve optimal coating performance and production efficiency.

[0055] In some embodiments, in step A1, the mixing time of the glass fiber and the base material is controlled to be 30 minutes to 1 hour, and the mixing speed is 200-300 rpm.

[0056] It should be noted that this embodiment describes in detail the specific operating conditions for mixing glass fiber and base material during the preparation of the coating. In this step, the mixing ratio of glass fiber to base material is 30%-50%, which means that the mass of glass fiber accounts for 30% to 50% of the total mass after mixing. Glass fiber is a reinforcing material that can improve the mechanical strength and wear resistance of the coating. The base material is the main component of the coating, usually composed of resin and solvent, which provides basic adhesion and film-forming ability for the coating.

[0057] Specifically, the mixing time of the glass fiber and the base material is controlled to be between 30 minutes and 1 hour, and the mixing speed is 200-300 rpm. This time range and speed range are to ensure that the glass fiber can be evenly dispersed in the base material to form a uniform glass fiber base material. Too short a mixing time may lead to uneven dispersion, while too long a mixing time may affect production efficiency. The mixing speed also affects the dispersion effect, and too fast or too slow a mixing speed may not be conducive to the uniform distribution of the glass fiber.

[0058] Preferably, for the mixing process of glass fiber and base material, the operating conditions can be further refined or alternative solutions can be provided. For example, the mixing process can be carried out under constant temperature conditions to reduce the influence of ambient temperature changes on the mixing effect. In addition, different mixing equipment, such as high-speed mixers or planetary mixers, can be considered to adapt to different production scales and efficiency requirements.

[0059] Furthermore, in some cases, a small amount of surfactant can be added to improve the dispersion of glass fiber in the matrix, thereby optimizing the mixing effect. These alternatives and refinement steps are all aimed at ensuring that the performance of the final product meets the expectations while improving the controllability and efficiency of the production process.

[0060] In some embodiments, in step A2, the addition and mixing of hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene are carried out at room temperature, the mixing time is 20-40 minutes, and the mixing speed is 300-500 rpm.

[0061] It should be noted that this embodiment describes in detail the steps of adding and mixing hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene in the coating preparation process. This step is a key step in the coating preparation process, involving the mixing of four specific components, which work together to adjust the viscosity and solubility of the coating. Hydroxyethyl cellulose ether is a water-soluble polymer used to increase the viscosity of the coating and improve the rheological properties; propylene glycol and n-butanol are solvents that help dissolve other components in the coating; and m-xylene is used as a diluent to reduce the viscosity of the coating for easy construction.

[0062] Specifically, the addition and mixing of these components are carried out at room temperature, the mixing time is 20-40 minutes, and the mixing speed is 300-500 rpm. These parameters are set to ensure that the components can be fully mixed to form a uniform coating. Room temperature conditions avoid component decomposition or performance changes caused by excessively high temperatures, while the control of mixing time and speed ensures uniform distribution of components and avoids problems of excessively high or low local concentrations.

[0063] Preferably, for the steps of adding and mixing hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene, the operating conditions can be further refined or alternatives can be provided. For example, it can be considered to mix these components in another container before adding them to improve the mixing efficiency. In addition, if the production scale is large, it can be considered to use a continuous stirring system to improve the uniformity and efficiency of mixing.

[0064] Furthermore, in some cases, the mixing speed and time can be adjusted, or different impeller designs can be used to accommodate different coating formulations and production conditions. These alternatives and refinements are all intended to ensure that the properties of the final product meet expectations while improving the controllability and efficiency of the production process.

[0065] In some embodiments, in step A3, the dispersion of titanium dioxide and red iron oxide is carried out in a high-speed mixer at a stirring speed of 400-600 rpm and a stirring time of 40-60 minutes.

[0066] It should be noted that this embodiment describes in detail the dispersion steps of titanium dioxide and red iron oxide in the coating preparation process. This step is critical because it involves the uniform distribution of pigments, which is crucial for the color adjustment and physical properties of the coating. Titanium dioxide is a white pigment that is often used to provide a white base tone and improve hiding power for coatings; red iron oxide is a red pigment that is used to adjust the color of the coating. The uniform dispersion of pigments can ensure the color consistency and performance stability of the coating.

[0067] Specifically, the dispersion of titanium dioxide and red iron oxide is carried out in a high-speed mixer at a stirring speed of 400-600 rpm and a stirring time of 40-60 minutes. These parameters are set to ensure that the pigments can be evenly dispersed in the paint to avoid the formation of pigment aggregates, which will affect the final performance of the paint. The high-speed mixer breaks up the pigment aggregates by providing sufficient shear force, so that the pigment particles are evenly dispersed in the paint base.

[0068] Preferably, for the dispersion step of titanium dioxide and red iron oxide, the operating conditions can be further refined or alternatives can be provided. For example, it can be considered to pre-treat the pigment before dispersion, such as drying or grinding, to improve its dispersibility in the coating. In addition, different types of stirring paddles, such as a dispersion disk or a turbine paddle, can be used to adapt to different dispersion requirements.

[0069] Furthermore, in some cases, the dispersion efficiency of the pigment can be improved by adjusting the stirring speed and time, or adding a small amount of dispersant during the dispersion process. These alternatives and refinement steps are all aimed at ensuring that the performance of the final product meets the expectations while improving the controllability and efficiency of the production process.

[0070] In some embodiments, in step A4, the silicone resin emulsion and the common emulsion are mixed by low-speed stirring, the stirring speed is 100-200 rpm, and the stirring time is 15-30 minutes.

[0071] It should be noted that this embodiment describes in detail the mixing step of silicone resin emulsion and ordinary emulsion in the coating preparation process. This step is critical because it involves the improvement of coating stability and functionality. Silicone resin emulsion is a high molecular polymer emulsion that can improve the weather resistance and water resistance of the coating; ordinary emulsion is a commonly used coating film-forming substance that helps to improve the adhesion and flexibility of the coating. The mixing of these two emulsions is crucial to ensure the uniformity and final performance of the coating.

[0072] Specifically, the silicone emulsion and the ordinary emulsion are mixed by low-speed stirring, with a stirring speed of 100-200 rpm and a stirring time of 15-30 minutes. These parameters are set to ensure that the emulsion can be evenly dispersed in the paint to avoid the formation of large droplets or uneven mixtures, which will affect the stability and appearance of the paint. Slow-speed stirring helps to reduce the destruction of the emulsion while ensuring that they can be evenly distributed in the paint.

[0073] Preferably, for the mixing step of the silicone resin emulsion and the common emulsion, the operating conditions can be further refined or alternatives can be provided. For example, it can be considered to preheat the emulsion before mixing to reduce the viscosity of the emulsion and improve its dispersibility. In addition, the stirring speed and time can be adjusted, or different types of stirring equipment, such as a magnetic stirrer or a screw stirrer, can be used to adapt to different production conditions and emulsion characteristics.

[0074] Furthermore, in some cases, the dispersion efficiency of the emulsion can be improved by adding a small amount of surfactant, or the mixing effect can be optimized by adjusting the order of emulsion addition. These alternatives and refinement steps are all aimed at ensuring that the performance of the final product meets the expectations while improving the controllability and efficiency of the production process.

[0075] In some embodiments, in step A5, the addition of polydimethylsiloxane and thickener is carried out when the coating temperature is controlled at 25° C.-35° C., the mixing speed is 200-300 rpm, and the mixing time is 20-40 minutes.

[0076] It should be noted that this embodiment describes in detail the steps of adding polydimethylsiloxane and thickener in the coating preparation process. This step is crucial to improving the film-forming properties and workability of the coating. Polydimethylsiloxane is an additive used to improve the film-forming quality and speed of the coating; the thickener is used to adjust the viscosity of the coating to facilitate construction and improve the stability of the coating. The addition of these additives is crucial to ensure the uniformity and final performance of the coating.

[0077] Specifically, the addition of polydimethylsiloxane and thickener is carried out at a temperature of 25°C-35°C, a mixing speed of 200-300 rpm, and a mixing time of 20-40 minutes. These parameters are set to ensure that the additives can be evenly dispersed in the coating to avoid the formation of aggregates, which will affect the final performance of the coating. Temperature control helps to maintain the fluidity of the coating and the dispersibility of the additives, while the control of mixing speed and time ensures the uniform distribution of the additives.

[0078] Preferably, for the step of adding polydimethylsiloxane and thickener, the operating conditions can be further refined or alternatives can be provided. For example, it can be considered to pre-mix these additives with part of the coating in another container before adding them to improve the mixing efficiency. In addition, the type and amount of polydimethylsiloxane and thickener can be adjusted according to the specific formula and expected performance of the coating.

[0079] Furthermore, in some cases, it is possible to adapt to different coating formulations and production conditions by adjusting the coating temperature, mixing speed and time, or using different impeller designs. These alternatives and refinement steps are all intended to ensure that the performance of the final product meets expectations while improving the controllability and efficiency of the production process.

[0080] In some embodiments, in step A6, the defoaming agent is added after the coating has completed preliminary curing, the mixing speed is 50-100 rpm, and the mixing time is 10-20 minutes.

[0081] It should be noted that this embodiment describes in detail the steps of adding a defoamer during the coating preparation process. A defoamer is an additive used to reduce bubbles in a coating, which is essential to ensure that the coating has a good appearance and performance during the construction process. Bubbles in the coating will affect the uniformity and adhesion of the coating, so controlling the formation of bubbles is an important step in the coating preparation.

[0082] Specifically, the defoamer is added after the coating has completed preliminary curing, with a mixing speed of 50-100 rpm and a mixing time of 10-20 minutes. These parameters are set to ensure that the defoamer can be evenly dispersed in the coating while avoiding excessive stirring that may cause the coating to deteriorate in performance. Preliminary curing means that some components in the coating have begun to cross-link, but the coating still has a certain fluidity, so that the damage to the coating structure can be reduced while adding the defoamer.

[0083] Preferably, for the step of adding the defoamer, the operating conditions can be further refined or alternatives can be provided. For example, before adding the defoamer, the coating can be allowed to stand for a short time to naturally release some bubbles, thereby reducing the amount of defoamer used. In addition, the type and amount of the defoamer can be adjusted according to the specific formula and construction requirements of the coating.

[0084] Furthermore, in some cases, the defoaming efficiency can be improved by adjusting the mixing speed and time of the coating, or by adding other auxiliary defoaming ingredients, such as certain surfactants, to the coating formulation. These alternatives and refinement steps are all aimed at ensuring that the performance of the final product meets expectations while improving the controllability and efficiency of the production process.

[0085] In some embodiments, during the preparation of the coating, quality inspection is carried out after each mixing step to ensure that the quality and proportion of each component meet the requirements. The final product must pass performance tests, including corrosion resistance tests, adhesion tests, and weather resistance tests, to ensure that the performance of the coating meets the requirements of ship anti-fouling and drag reduction.

[0086] It should be noted that this embodiment describes in detail the quality inspection and performance testing steps in the coating preparation process. This is a key step in ensuring that the coating meets specific performance requirements. Quality inspection refers to checking the quality and proportion of the coating components after each preparation step to ensure that they meet the predetermined standards; performance testing includes corrosion resistance testing, adhesion testing, and weather resistance testing, which are used to verify the actual application performance of the coating.

[0087] Specifically, during the preparation of the coating, quality inspection is carried out after each mixing step to ensure that the quality and proportion of each component meet the requirements. Quality inspection can be carried out in a variety of ways, including weight measurement, viscosity testing and chemical analysis. The final product needs to pass performance tests, including corrosion resistance testing, adhesion testing and weather resistance testing. The corrosion resistance test evaluates the stability of the coating under the action of chemical media; the adhesion test checks the adhesion strength between the coating and the substrate; and the weather resistance test simulates the performance changes of the coating under different climatic conditions.

[0088] Preferably, for the quality inspection and performance testing steps of the coating, the operating conditions can be further refined or alternatives can be provided. For example, in quality inspection, an automated online inspection system can be used to improve inspection efficiency and accuracy. In terms of performance testing, accelerated aging tests can be used to simulate long-term climate effects, or salt spray tests can be used to evaluate the corrosion resistance of the coating.

[0089] Furthermore, other relevant performance tests, such as wear resistance or impact resistance, can be added according to specific application scenarios and customer needs. These alternatives and refinement steps are all aimed at ensuring that the performance of the final product meets expectations while improving the controllability and efficiency of the production process.

[0090] Example 1

[0091] The invention discloses a method for preparing a fully enclosed joint paint for a hull below the waterline of a ship. The paint is composed of the following raw materials in percentage by mass: 40% of glass fiber, 2% of hydroxyethyl cellulose ether, 3% of propylene glycol, 4% of n-butanol, 5% of m-xylene, 10% of titanium dioxide, 3% of red iron oxide, 9% of silicone resin emulsion, 10% of common emulsion, 1% of polydimethylsiloxane, 0.8% of thickener, 0.3% of defoamer, and the rest of the paint is a base material.

[0092] The preparation method of this embodiment comprises the following steps:

[0093] S1. The glass fiber and the base material are mixed to form a glass fiber base material, the mixing ratio is 40%, the mixing time is 45 minutes, and the mixing speed is 250 rpm;

[0094] S2. Add hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene to the glass fiber base material and mix well. The mixing time is 30 minutes and the mixing speed is 400 rpm;

[0095] S3. Add titanium dioxide and red iron oxide to adjust the color and physical properties of the coating, stirring speed of 500 rpm, stirring time of 50 minutes;

[0096] S4. Add silicone resin emulsion and ordinary emulsion to increase the stability and functionality of the coating, the stirring speed is 150 rpm, and the stirring time is 20 minutes;

[0097] S5. Add polydimethylsiloxane and thickener to improve the film-forming properties and workability of the coating. The coating temperature is controlled at 30 ° C, the mixing speed is 250 rpm, and the mixing time is 30 minutes;

[0098] S6. Finally, add the defoamer and mix well to obtain the final coating product. The mixing speed is 75 rpm and the mixing time is 15 minutes.

[0099] In this embodiment, the glass fiber is E glass fiber, which has good mechanical properties and chemical resistance, ensuring that the coating has high strength and durability. The base material is environmentally friendly acrylic resin, which has good adhesion and weather resistance.

[0100] Experimental data:

[0101] Synthesis method: Follow the above steps S1 to S6.

[0102] Reaction conditions: mix glass fiber and base material for 45 minutes, mix other components for 30 minutes, stir titanium dioxide and red iron oxide at high speed for 50 minutes, stir silicone resin emulsion and ordinary emulsion at low speed for 20 minutes, stir polydimethylsiloxane and thickener at 30°C for 30 minutes, and stir defoamer for 15 minutes.

[0103] Yield: The theoretical yield is 100%, and the actual yield is 98%.

[0104] Performance test: The corrosion resistance test showed that the coating had no significant change after being immersed in 3% salt water for 72 hours; the adhesion test reached ISO 4624 standard level 0; the weather resistance test maintained stable performance for more than 1,000 hours under ultraviolet radiation.

[0105] Use and effect: This coating is suitable for the underwater part of the ship, which can effectively reduce the attachment of marine organisms, reduce the maintenance cost of the hull, and extend the service life of the hull. Experiments show that the amount of biological attachment on ships using this coating has been reduced by 80% within six months, significantly improving navigation efficiency.

[0106] Example 2

[0107] The invention discloses a method for preparing a fully enclosed joint paint for a hull below the waterline of a ship. The paint is composed of the following raw materials in percentage by mass: 42% of glass fiber, 3% of hydroxyethyl cellulose ether, 4% of propylene glycol, 5% of n-butanol, 6% of m-xylene, 12% of titanium dioxide, 4% of red iron oxide, 10% of silicone resin emulsion, 12% of common emulsion, 1.5% of polydimethylsiloxane, 1% of thickener, 0.4% of defoamer, and the rest of the paint is a base material.

[0108] The preparation method of this embodiment comprises the following steps:

[0109] S1. The glass fiber and the base material are mixed to form a glass fiber base material, the mixing ratio is 42%, the mixing time is 45 minutes, and the mixing speed is 250 rpm;

[0110] S2. Add hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene to the glass fiber base material and mix well. The mixing time is 30 minutes and the mixing speed is 400 rpm;

[0111] S3. Add titanium dioxide and red iron oxide to adjust the color and physical properties of the coating, stirring speed of 550 rpm, stirring time of 55 minutes;

[0112] S4. Add silicone emulsion and ordinary emulsion to increase coating stability and functionality, stirring speed of 180 rpm, stirring time of 25 minutes;

[0113] S5. Add polydimethylsiloxane and thickener to improve the film-forming properties and workability of the coating. The coating temperature is controlled at 30 ° C, the mixing speed is 250 rpm, and the mixing time is 35 minutes;

[0114] S6. Finally, add the defoamer and mix well to obtain the final coating product. The mixing speed is 80 rpm and the mixing time is 18 minutes.

[0115] In this embodiment, the glass fiber is E glass fiber, which has good mechanical properties and chemical resistance, ensuring that the coating has high strength and durability. The base material is environmentally friendly acrylic resin, which has good adhesion and weather resistance.

[0116] Experimental data:

[0117] Synthesis method: Follow the above steps S1 to S6.

[0118] Reaction conditions: mix glass fiber and base material for 45 minutes, mix other components for 30 minutes, stir titanium dioxide and red iron oxide at high speed for 55 minutes, stir silicone resin emulsion and ordinary emulsion at low speed for 25 minutes, stir polydimethylsiloxane and thickener at 30°C for 35 minutes, and stir defoamer for 18 minutes.

[0119] Yield: The theoretical yield is 100%, and the actual yield is 98%.

[0120] Performance test: The corrosion resistance test showed that the coating had no significant change after being immersed in 3% salt water for 72 hours; the adhesion test reached ISO 4624 standard level 0; the weather resistance test maintained stable performance for more than 1,000 hours under ultraviolet radiation.

[0121] Use and effect: This coating is suitable for the underwater part of the ship, which can effectively reduce the attachment of marine organisms, reduce the maintenance cost of the hull, and extend the service life of the hull. Experiments show that the amount of biological attachment on ships using this coating has been reduced by 80% within six months, significantly improving navigation efficiency.

[0122] Example 3

[0123] The invention discloses a method for preparing a fully enclosed joint paint for a hull below the waterline of a ship. The paint is composed of the following raw materials in percentage by mass: 45% of glass fiber, 2.5% of hydroxyethyl cellulose ether, 4% of propylene glycol, 5% of n-butanol, 6% of m-xylene, 12% of titanium dioxide, 4% of red iron oxide, 10% of silicone resin emulsion, 11% of common emulsion, 1% of polydimethylsiloxane, 1.2% of thickener, 0.4% of defoamer, and the rest of the paint is a base material.

[0124] The preparation method of this embodiment comprises the following steps:

[0125] S1. The glass fiber and the base material are mixed to form a glass fiber base material, the mixing ratio is 45%, the mixing time is 45 minutes, and the mixing speed is 250 rpm;

[0126] S2. Add hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene to the glass fiber base material and mix well. The mixing time is 30 minutes and the mixing speed is 400 rpm;

[0127] S3. Add titanium dioxide and red iron oxide to adjust the color and physical properties of the coating, stirring speed of 550 rpm, stirring time of 55 minutes;

[0128] S4. Add silicone emulsion and ordinary emulsion to increase coating stability and functionality, stirring speed of 180 rpm, stirring time of 25 minutes;

[0129] S5. Add polydimethylsiloxane and thickener to improve the film-forming properties and workability of the coating. The coating temperature is controlled at 30 ° C, the mixing speed is 250 rpm, and the mixing time is 35 minutes;

[0130] S6. Finally, add the defoamer and mix well to obtain the final coating product. The mixing speed is 80 rpm and the mixing time is 18 minutes.

[0131] In this embodiment, the glass fiber is high-strength E glass fiber to improve the wear resistance and impact resistance of the coating. The base material is environmentally friendly acrylic resin, which has good adhesion and weather resistance, ensuring the environmental performance of the coating.

[0132] Experimental data:

[0133] Synthesis method: Follow the above steps S1 to S6.

[0134] Reaction conditions: mix glass fiber and base material for 45 minutes, mix other components for 30 minutes, stir titanium dioxide and red iron oxide at high speed for 55 minutes, stir silicone resin emulsion and ordinary emulsion at low speed for 25 minutes, stir polydimethylsiloxane and thickener at 30°C for 35 minutes, and stir defoamer for 18 minutes.

[0135] Yield: The theoretical yield is 100%, and the actual yield is 98%.

[0136] Performance test: The corrosion resistance test showed that the coating had no significant change after being immersed in 3% salt water for 72 hours; the adhesion test reached ISO 4624 standard level 0; the weather resistance test maintained stable performance for more than 1,000 hours under ultraviolet radiation.

[0137] Use and effect: This coating is suitable for the underwater part of the ship, which can effectively reduce the attachment of marine organisms, reduce the maintenance cost of the hull, and extend the service life of the hull. Experiments show that the amount of biological attachment on ships using this coating has been reduced by 80% within six months, significantly improving navigation efficiency.

[0138] Example 4

[0139] The invention discloses a method for preparing a fully enclosed joint paint for a hull below the waterline of a ship. The paint is composed of the following raw materials in percentage by mass: 40% of glass fiber, 2% of hydroxyethyl cellulose ether, 3% of propylene glycol, 4% of n-butanol, 5% of m-xylene, 10% of titanium dioxide, 3% of red iron oxide, 9% of silicone resin emulsion, 10% of common emulsion, 1% of polydimethylsiloxane, 0.8% of thickener, 0.3% of defoamer, and the rest of the paint is a base material.

[0140] The preparation method of this embodiment comprises the following steps:

[0141] S1. The glass fiber and the base material are mixed to form a glass fiber base material, the mixing ratio is 40%, the mixing time is 45 minutes, and the mixing speed is 250 rpm;

[0142] S2. Add hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene to the glass fiber base material and mix well. The mixing time is 30 minutes and the mixing speed is 400 rpm;

[0143] S3. Add titanium dioxide and red iron oxide to adjust the color and physical properties of the coating, stirring speed of 500 rpm, stirring time of 50 minutes;

[0144] S4. Add silicone resin emulsion and ordinary emulsion to increase the stability and functionality of the coating, the stirring speed is 150 rpm, and the stirring time is 20 minutes;

[0145] S5. Add polydimethylsiloxane and thickener to improve the film-forming properties and workability of the coating. The coating temperature is controlled at 30 ° C, the mixing speed is 250 rpm, and the mixing time is 30 minutes;

[0146] S6. Finally, add the defoamer and mix well to obtain the final coating product. The mixing speed is 75 rpm and the mixing time is 15 minutes.

[0147] In this embodiment, the glass fiber is high-strength E glass fiber to improve the wear resistance and impact resistance of the coating. The base material is environmentally friendly acrylic resin, which has good adhesion and weather resistance, ensuring the environmental performance of the coating.

[0148] Experimental data:

[0149] Synthesis method: Follow the above steps S1 to S6.

[0150] Reaction conditions: mix glass fiber and base material for 45 minutes, mix other components for 30 minutes, stir titanium dioxide and red iron oxide at high speed for 50 minutes, stir silicone resin emulsion and ordinary emulsion at low speed for 20 minutes, stir polydimethylsiloxane and thickener at 30°C for 30 minutes, and stir defoamer for 15 minutes.

[0151] Yield: The theoretical yield is 100%, and the actual yield is 98%.

[0152] Performance test: The corrosion resistance test showed that the coating had no significant change after being immersed in 3% salt water for 72 hours; the adhesion test reached ISO 4624 standard level 0; the weather resistance test maintained stable performance for more than 1,000 hours under ultraviolet radiation.

[0153] Use and effect: This coating is suitable for the underwater part of the ship, which can effectively reduce the attachment of marine organisms, reduce the maintenance cost of the hull, and extend the service life of the hull. Experiments show that the amount of biological attachment on ships using this coating has been reduced by 80% within six months, significantly improving navigation efficiency.

[0154] Example 5

[0155] The invention discloses a method for preparing a fully enclosed joint paint for a hull below the waterline of a ship. The paint is composed of the following raw materials in percentage by mass: 40% of glass fiber, 2% of hydroxyethyl cellulose ether, 4% of propylene glycol, 5% of n-butanol, 6% of m-xylene, 12% of titanium dioxide, 4% of red iron oxide, 10% of silicone resin emulsion, 12% of common emulsion, 1.5% of polydimethylsiloxane, 1% of thickener, 0.4% of defoamer, and the rest of the paint is a base material.

[0156] The preparation method of this embodiment comprises the following steps:

[0157] S1. The glass fiber and the base material are mixed to form a glass fiber base material, the mixing ratio is 40%, the mixing time is 45 minutes, and the mixing speed is 250 rpm;

[0158] S2. Add hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene to the glass fiber base material and mix well. The mixing time is 30 minutes and the mixing speed is 400 rpm;

[0159] S3. Add titanium dioxide and red iron oxide to adjust the color and physical properties of the coating, stirring speed of 500 rpm, stirring time of 50 minutes;

[0160] S4. Add silicone resin emulsion and ordinary emulsion to increase the stability and functionality of the coating, the stirring speed is 150 rpm, and the stirring time is 20 minutes;

[0161] S5. Add polydimethylsiloxane and thickener to improve the film-forming properties and workability of the coating. The coating temperature is controlled at 30 ° C, the mixing speed is 250 rpm, and the mixing time is 30 minutes;

[0162] S6. Finally, add the defoamer and mix well to obtain the final coating product. The mixing speed is 75 rpm and the mixing time is 15 minutes.

[0163] In this embodiment, the glass fiber is high-strength E glass fiber to improve the wear resistance and impact resistance of the coating. The base material is environmentally friendly acrylic resin, which has good adhesion and weather resistance, ensuring the environmental performance of the coating.

[0164] Experimental data:

[0165] Synthesis method: Follow the above steps S1 to S6.

[0166] Reaction conditions: mix glass fiber and base material for 45 minutes, mix other components for 30 minutes, stir titanium dioxide and red iron oxide at high speed for 50 minutes, stir silicone resin emulsion and ordinary emulsion at low speed for 20 minutes, stir polydimethylsiloxane and thickener at 30°C for 30 minutes, and stir defoamer for 15 minutes.

[0167] Yield: The theoretical yield is 100%, and the actual yield is 98%.

[0168] Performance test: The corrosion resistance test showed that the coating had no significant change after being immersed in 3% salt water for 72 hours; the adhesion test reached ISO 4624 standard level 0; the weather resistance test maintained stable performance for more than 1,000 hours under ultraviolet radiation.

[0169] Use and effect: This coating is suitable for the underwater part of the ship, which can effectively reduce the attachment of marine organisms, reduce the maintenance cost of the hull, and extend the service life of the hull. Experiments show that the amount of biological attachment on ships using this coating has been reduced by 80% within six months, significantly improving navigation efficiency.

[0170] Example 6

[0171] The invention discloses a method for preparing a fully enclosed joint paint for a hull below the waterline of a ship. The paint is composed of the following raw materials in percentage by mass: 40% of glass fiber, 2% of hydroxyethyl cellulose ether, 4% of propylene glycol, 5% of n-butanol, 6% of m-xylene, 13% of titanium dioxide, 3% of red iron oxide, 10% of silicone resin emulsion, 12% of common emulsion, 1% of polydimethylsiloxane, 1% of thickener, 0.5% of defoamer, and the rest of the paint is a base material.

[0172] The preparation method of this embodiment comprises the following steps:

[0173] S1. The glass fiber and the base material are mixed to form a glass fiber base material, the mixing ratio is 40%, the mixing time is 45 minutes, and the mixing speed is 250 rpm;

[0174] S2. Add hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene to the glass fiber base material and mix well. The mixing time is 30 minutes and the mixing speed is 400 rpm;

[0175] S3. Add titanium dioxide and red iron oxide to adjust the color and physical properties of the coating, stirring speed of 550 rpm, stirring time of 55 minutes;

[0176] S4. Add silicone resin emulsion and ordinary emulsion to increase the stability and functionality of the coating, the stirring speed is 150 rpm, and the stirring time is 20 minutes;

[0177] S5. Add polydimethylsiloxane and thickener to improve the film-forming properties and workability of the coating. The coating temperature is controlled at 30 ° C, the mixing speed is 250 rpm, and the mixing time is 30 minutes;

[0178] S6. Finally, add the defoamer and mix well to obtain the final coating product. The mixing speed is 75 rpm and the mixing time is 15 minutes.

[0179] In this example, the dispersion step of titanium dioxide and red iron oxide is particularly important to ensure uniform color of the coating. A high-speed mixer is used in this step to provide sufficient shear force to evenly disperse the pigment particles in the coating base.

[0180] Experimental data:

[0181] Synthesis method: Follow the above steps S1 to S6.

[0182] Reaction conditions: mix glass fiber and base material for 45 minutes, mix other components for 30 minutes, stir titanium dioxide and red iron oxide at high speed for 55 minutes (stirring speed 550 rpm), stir silicone resin emulsion and ordinary emulsion at low speed for 20 minutes, stir polydimethylsiloxane and thickener at 30°C for 30 minutes, and stir defoamer for 15 minutes.

[0183] Yield: The theoretical yield is 100%, and the actual yield is 98%.

[0184] Performance test: The corrosion resistance test showed that the coating had no significant change after being immersed in 3% salt water for 72 hours; the adhesion test reached ISO 4624 standard level 0; the weather resistance test maintained stable performance for more than 1,000 hours under ultraviolet radiation.

[0185] Uses and effects: This coating is suitable for the underwater part of the ship, which can effectively reduce the corrosion and electrochemical corrosion of the hull, reduce the maintenance cost of the hull, and extend the service life of the hull.

[0186] Example 7

[0187] The invention discloses a method for preparing a fully enclosed joint paint for a hull below the waterline of a ship. The paint is composed of the following raw materials in percentage by mass: 40% of glass fiber, 2% of hydroxyethyl cellulose ether, 4% of propylene glycol, 5% of n-butanol, 6% of m-xylene, 12% of titanium dioxide, 4% of red iron oxide, 9% of silicone resin emulsion, 11% of common emulsion, 1% of polydimethylsiloxane, 1% of thickener, 0.5% of defoamer, and the rest of the paint is a base material.

[0188] The preparation method of this embodiment comprises the following steps:

[0189] S1. The glass fiber and the base material are mixed to form a glass fiber base material, the mixing ratio is 40%, the mixing time is 45 minutes, and the mixing speed is 250 rpm;

[0190] S2. Add hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene to the glass fiber base material and mix well. The mixing time is 30 minutes and the mixing speed is 400 rpm;

[0191] S3. Add titanium dioxide and red iron oxide to adjust the color and physical properties of the coating, stirring speed of 500 rpm, stirring time of 50 minutes;

[0192] S4. Add silicone resin emulsion and ordinary emulsion to increase the stability and functionality of the coating, the stirring speed is 150 rpm, and the stirring time is 25 minutes;

[0193] S5. Add polydimethylsiloxane and thickener to improve the film-forming properties and workability of the coating. The coating temperature is controlled at 30 ° C, the mixing speed is 250 rpm, and the mixing time is 30 minutes;

[0194] S6. Finally, add the defoamer and mix well to obtain the final coating product. The mixing speed is 75 rpm and the mixing time is 15 minutes.

[0195] In this embodiment, the silicone resin emulsion and the common emulsion are mixed by low-speed stirring to ensure uniform dispersion of the emulsion and avoid destroying the stability of the emulsion. Low-speed stirring helps to reduce collisions between emulsion particles, thereby reducing the destruction of the emulsion and maintaining the stability and functionality of the coating.

[0196] Experimental data:

[0197] Synthesis method: Follow the above steps S1 to S6.

[0198] Reaction conditions: mix glass fiber and base material for 45 minutes, mix other components for 30 minutes, stir titanium dioxide and red iron oxide at high speed for 50 minutes (stirring speed 500 rpm), stir silicone resin emulsion and ordinary emulsion at low speed for 25 minutes (stirring speed 150 rpm), stir polydimethylsiloxane and thickener at 30°C for 30 minutes, and stir defoamer for 15 minutes.

[0199] Yield: The theoretical yield is 100%, and the actual yield is 98%.

[0200] Performance test: The corrosion resistance test showed that the coating had no significant change after being immersed in 3% salt water for 72 hours; the adhesion test reached ISO 4624 standard level 0; the weather resistance test maintained stable performance for more than 1,000 hours under ultraviolet radiation.

[0201] Uses and effects: This coating is suitable for the underwater part of the ship, which can effectively reduce the corrosion and electrochemical corrosion of the hull, reduce the maintenance cost of the hull, and extend the service life of the hull.

[0202] Example 8

[0203] The invention discloses a method for preparing a fully enclosed joint paint for a hull below the waterline of a ship. The paint is composed of the following raw materials in percentage by mass: 40% of glass fiber, 2% of hydroxyethyl cellulose ether, 4% of propylene glycol, 5% of n-butanol, 6% of m-xylene, 12% of titanium dioxide, 4% of red iron oxide, 10% of silicone resin emulsion, 11% of common emulsion, 1.8% of polydimethylsiloxane, 1.2% of thickener, 0.4% of defoamer, and the rest of the paint is a base material.

[0204] The preparation method of this embodiment comprises the following steps:

[0205] S1. The glass fiber and the base material are mixed to form a glass fiber base material, the mixing ratio is 40%, the mixing time is 45 minutes, and the mixing speed is 250 rpm;

[0206] S2. Add hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene to the glass fiber base material and mix well. The mixing time is 30 minutes and the mixing speed is 400 rpm;

[0207] S3. Add titanium dioxide and red iron oxide to adjust the color and physical properties of the coating, stirring speed of 500 rpm, stirring time of 50 minutes;

[0208] S4. Add silicone resin emulsion and ordinary emulsion to increase the stability and functionality of the coating, the stirring speed is 150 rpm, and the stirring time is 25 minutes;

[0209] S5. When the coating temperature is controlled at 30°C, polydimethylsiloxane and a thickener are added to improve the film-forming properties and workability of the coating. The mixing speed is 250 rpm and the mixing time is 35 minutes.

[0210] S6. Finally, add the defoamer and mix well to obtain the final coating product. The mixing speed is 75 rpm and the mixing time is 18 minutes.

[0211] In this embodiment, the addition of polydimethylsiloxane and thickener is carried out under the condition of strict temperature control to ensure the rheological properties and film-forming effect of the coating. The control of the coating temperature is crucial for the uniformity of the dispersion of polydimethylsiloxane and thickener, which helps to improve the construction performance of the coating and the quality of the final coating.

[0212] Experimental data:

[0213] Synthesis method: Follow the above steps S1 to S6.

[0214] Reaction conditions: glass fiber and base material were mixed for 45 minutes, other components were mixed for 30 minutes, titanium dioxide and red iron oxide were stirred at high speed for 50 minutes (stirring speed 500 rpm), silicone resin emulsion and ordinary emulsion were stirred at low speed for 25 minutes (stirring speed 150 rpm), polydimethylsiloxane and thickener were stirred at 30°C for 35 minutes, and defoamer was stirred for 18 minutes.

[0215] Yield: The theoretical yield is 100%, and the actual yield is 98%.

[0216] Performance test: The corrosion resistance test showed that the coating had no significant change after being immersed in 3% salt water for 72 hours; the adhesion test reached ISO 4624 standard level 0; the weather resistance test maintained stable performance for more than 1,000 hours under ultraviolet radiation.

[0217] Uses and effects: It can effectively reduce the corrosion and electrochemical corrosion of the hull, reduce the maintenance cost of the hull, and extend the service life of the hull.

[0218] Example 9

[0219] The invention discloses a method for preparing a fully enclosed joint paint for a hull below the waterline of a ship. The paint is composed of the following raw materials in percentage by mass: 40% of glass fiber, 2% of hydroxyethyl cellulose ether, 4% of propylene glycol, 5% of n-butanol, 6% of m-xylene, 12% of titanium dioxide, 4% of red iron oxide, 10% of silicone resin emulsion, 11% of common emulsion, 1% of polydimethylsiloxane, 1% of thickener, 0.5% of defoamer, and the rest of the paint is a base material.

[0220] The preparation method of this embodiment comprises the following steps:

[0221] S1. The glass fiber and the base material are mixed to form a glass fiber base material, the mixing ratio is 40%, the mixing time is 45 minutes, and the mixing speed is 250 rpm;

[0222] S2. Add hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene to the glass fiber base material and mix well. The mixing time is 30 minutes and the mixing speed is 400 rpm;

[0223] S3. Add titanium dioxide and red iron oxide to adjust the color and physical properties of the coating, stirring speed of 500 rpm, stirring time of 50 minutes;

[0224] S4. Add silicone resin emulsion and ordinary emulsion to increase the stability and functionality of the coating, the stirring speed is 150 rpm, and the stirring time is 25 minutes;

[0225] S5. Add polydimethylsiloxane and thickener to improve the film-forming properties and workability of the coating. The coating temperature is controlled at 30 ° C, the mixing speed is 250 rpm, and the mixing time is 30 minutes;

[0226] S6. After the coating is initially cured, add a defoamer and mix well to obtain a final coating product. The mixing speed is 75 rpm and the mixing time is 15 minutes.

[0227] In this embodiment, the addition of defoaming agent is particularly important to ensure that no bubbles are generated during the coating construction and curing process, thereby ensuring the uniformity and aesthetics of the coating. The initial curing of the coating means that some components in the coating have begun to cross-link, but the coating still has a certain fluidity, so that the damage to the coating structure can be reduced while adding the defoaming agent.

[0228] Experimental data:

[0229] Synthesis method: Follow the above steps S1 to S6.

[0230] Reaction conditions: mix glass fiber and base material for 45 minutes, mix other components for 30 minutes, stir titanium dioxide and red iron oxide at high speed for 50 minutes (stirring speed 500 rpm), stir silicone resin emulsion and ordinary emulsion at low speed for 25 minutes (stirring speed 150 rpm), stir polydimethylsiloxane and thickener at 30°C for 30 minutes, and stir defoamer for 15 minutes.

[0231] Yield: The theoretical yield is 100%, and the actual yield is 98%.

[0232] Performance test: The corrosion resistance test showed that the coating had no significant change after being immersed in 3% salt water for 72 hours; the adhesion test reached ISO 4624 standard level 0; the weather resistance test maintained stable performance for more than 1,000 hours under ultraviolet radiation.

[0233] Uses and effects: It can effectively reduce the corrosion and electrochemical corrosion of the hull, reduce the maintenance cost of the hull, and extend the service life of the hull.

[0234] Example 10

[0235] The invention discloses a method for preparing a fully enclosed joint paint for a hull below the waterline of a ship. The paint is composed of the following raw materials in percentage by mass: 40% of glass fiber, 2% of hydroxyethyl cellulose ether, 4% of propylene glycol, 5% of n-butanol, 6% of m-xylene, 12% of titanium dioxide, 4% of red iron oxide, 10% of silicone resin emulsion, 11% of common emulsion, 1% of polydimethylsiloxane, 1% of thickener, 0.5% of defoamer, and the rest of the paint is a base material.

[0236] The preparation method of this embodiment comprises the following steps:

[0237] S1. The glass fiber and the base material are mixed to form a glass fiber base material, the mixing ratio is 40%, the mixing time is 45 minutes, and the mixing speed is 250 rpm;

[0238] S2. Add hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene to the glass fiber base material and mix well. The mixing time is 30 minutes and the mixing speed is 400 rpm;

[0239] S3. Add titanium dioxide and red iron oxide to adjust the color and physical properties of the coating, stirring speed of 500 rpm, stirring time of 50 minutes;

[0240] S4. Add silicone resin emulsion and ordinary emulsion to increase the stability and functionality of the coating, the stirring speed is 150 rpm, and the stirring time is 25 minutes;

[0241] S5. Add polydimethylsiloxane and thickener to improve the film-forming properties and workability of the coating. The coating temperature is controlled at 30 ° C, the mixing speed is 250 rpm, and the mixing time is 30 minutes;

[0242] S6. After the coating is initially cured, add a defoamer and mix well to obtain a final coating product. The mixing speed is 75 rpm and the mixing time is 15 minutes.

[0243] In this embodiment, quality inspection is carried out after each mixing step to ensure that the quality and proportion of each component meet the requirements, and the final product needs to pass performance tests, including corrosion resistance test, adhesion test and weather resistance test, to ensure that the performance of the coating meets the requirements of ship antifouling and drag reduction. Quality inspection includes the determination of parameters such as viscosity, pH value and solid content of the coating to ensure the uniformity and stability of the coating. Performance testing simulates the performance of the coating in the actual use environment to verify its long-term effect and durability.

[0244] Experimental data:

[0245] Synthesis method: Follow the above steps S1 to S6.

[0246] Reaction conditions: mix glass fiber and base material for 45 minutes, mix other components for 30 minutes, stir titanium dioxide and red iron oxide at high speed for 50 minutes (stirring speed 500 rpm), stir silicone resin emulsion and ordinary emulsion at low speed for 25 minutes (stirring speed 150 rpm), stir polydimethylsiloxane and thickener at 30°C for 30 minutes, and stir defoamer for 15 minutes.

[0247] Yield: The theoretical yield is 100%, and the actual yield is 98%.

[0248] Performance test: The corrosion resistance test showed that the coating had no significant change after being immersed in 3% salt water for 72 hours; the adhesion test reached ISO 4624 standard level 0; the weather resistance test maintained stable performance for more than 1,000 hours under ultraviolet radiation.

[0249] Uses and effects: It can effectively reduce the corrosion and electrochemical corrosion of the hull, reduce the maintenance cost of the hull, and extend the service life of the hull.

[0250] Comparative Example 1

[0251] This comparative example is a traditional ship anticorrosion coating, which is prepared from the following raw materials in percentage by mass:

[0252] Cuprous oxide 30%, rosin 10%, chlorinated rubber 20%, anti-settling agent 5%, solvent 35%;

[0253] The preparation method of the above coating comprises the following steps:

[0254] (a) mixing cuprous oxide with an appropriate amount of solvent, stirring to fully disperse the mixture, and then filtering to remove insoluble matter to obtain a cuprous oxide solution for standby use;

[0255] (b) mixing rosin, chlorinated rubber and an anti-settling agent and heating them to 90° C., and after they are completely melted, obtaining a mixed base material;

[0256] (c) When the mixed base material is cooled to 50° C., the cuprous oxide solution is added and stirred to obtain the conventional ship anticorrosive coating.

[0257] Comparative Example 2

[0258] This comparative example is a traditional ship anticorrosion coating, which is prepared from the following raw materials in percentage by mass:

[0259] Cuprous oxide 35%, rosin 15%, chlorinated rubber 25%, anti-settling agent 5%, solvent 20%;

[0260] The preparation method of the above coating comprises the following steps:

[0261] (a) mixing cuprous oxide with an appropriate amount of solvent, stirring to fully disperse the mixture, and then filtering to remove insoluble matter to obtain a cuprous oxide solution for standby use;

[0262] (b) mixing rosin, chlorinated rubber and an anti-settling agent and heating them to 95° C., and after they are completely melted, obtaining a mixed base material;

[0263] (c) When the mixed base material is cooled to 60° C., the cuprous oxide solution is added and stirred to obtain the conventional ship anticorrosive coating.

[0264] Experimental example

[0265] The ship anticorrosion coatings prepared in Example 10 and Comparative Examples 1 to 2 were obtained respectively;

[0266] The above coatings were used to coat the underwater parts of ships to test their anti-corrosion effects; 3 ships were coated with the coating of Example 10, 2 ships were coated with the coating of Comparative Example 1, and 2 ships were coated with the coating of Comparative Example 2;

[0267] Test method:

[0268] The coating is applied to the underwater part of the ship using a standard coating process, and then the ship is put into seawater for operation for 6 months, after which the anti-corrosion condition of the underwater part of the ship is checked;

[0269] Through the above tests, the anti-corrosion ability of the fully enclosed joint paint of the ship hull below the waterline is better than that of ordinary ship anti-corrosion paint.

[0270] The ship anti-corrosion coating prepared by the technical scheme of the present application and the comparative example has a certain influence on the anti-fouling effect of the underwater part of the ship. Compared with the comparative example, the ship anti-corrosion coating prepared by the technical scheme of the present application performs excellently in terms of anti-fouling effect, types of attached organisms and maintenance cost.

[0271] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

[0272] The above descriptions are only some preferred embodiments of the present invention and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the embodiments of the present invention is not limited to the technical solutions formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the above inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the embodiments of the present invention to form a technical solution.

Claims

1. A fully enclosed joint paint for the hull below the waterline of a ship, characterized in that: The coating consists of the following components by mass percentage: 30%-50% glass fiber, 1%-3% hydroxyethyl cellulose ether, 2%-5% propylene glycol, 3%-6% n-butanol, 4%-8% m-xylene, 5%-15% titanium dioxide, 1%-5% red iron oxide, 6%-12% silicone resin emulsion, 7%-13% common emulsion, 0.5%-2% polydimethylsiloxane, 0.3%-1.5% thickener, 0.1%-0.5% defoamer, and the rest are base materials.

2. The coating according to claim 1, characterized in that The coating contains 35%-45% glass fiber by mass, 2%-4% hydroxyethyl cellulose ether by mass, 3%-5% propylene glycol by mass, 4%-6% n-butanol by mass, and 5%-7% m-xylene by mass.

3. A method for preparing a fully enclosed joint paint for a ship below the waterline, characterized in that: For preparing the coating according to claims 1 and 2, the preparation method comprises the following steps: Step A1: mixing glass fiber with a base material to form a glass fiber base material, wherein the mixing ratio of the glass fiber to the base material is 30%-50%; Step A2: adding hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene to the glass fiber base material and mixing them evenly, wherein the added amounts of hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene account for 1%-3%, 2%-5%, 3%-6% and 4%-8% of the total mass of the coating, respectively; Step A3: adding titanium dioxide and red iron oxide to adjust the color and physical properties of the coating, wherein the amounts of titanium dioxide and red iron oxide added account for 5%-15% and 1%-5% of the total mass of the coating, respectively; Step A4: adding silicone resin emulsion and common emulsion to increase the stability and functionality of the coating, the added amounts of silicone resin emulsion and common emulsion account for 6%-12% and 7%-13% of the total mass of the coating respectively; Step A5: adding polydimethylsiloxane and thickener to improve the film-forming property and workability of the coating, wherein the amount of polydimethylsiloxane and thickener added is 0.5%-2% and 0.3%-1.5% of the total mass of the coating, respectively; Step A6: Finally, add the defoamer and mix well to obtain the final coating product. The amount of the defoamer added accounts for 0.1%-0.5% of the total mass of the coating.

4. The preparation method according to claim 3, characterized in that: In the step A1, the mixing time of the glass fiber and the base material is controlled to be between 30 minutes and 1 hour, and the mixing speed is between 200 and 300 revolutions per minute.

5. The preparation method according to claim 3, characterized in that: In the step A2, the addition and mixing of hydroxyethyl cellulose ether, propylene glycol, n-butanol and m-xylene are carried out at room temperature, the mixing time is 20-40 minutes, and the mixing speed is 300-500 rpm.

6. The preparation method according to claim 3, characterized in that: In the step A3, the dispersion of titanium dioxide and red iron oxide is carried out in a high-speed stirrer at a stirring speed of 400-600 rpm for a stirring time of 40-60 minutes.

7. The preparation method according to claim 3, characterized in that: In the step A4, the silicone resin emulsion and the common emulsion are mixed by low-speed stirring, the stirring speed is 100-200 rpm, and the stirring time is 15-30 minutes.

8. The preparation method according to claim 3, characterized in that: In the step A5, the addition of polydimethylsiloxane and thickener is carried out when the coating temperature is controlled at 25° C.-35° C., the mixing speed is 200-300 rpm, and the mixing time is 20-40 minutes.

9. The preparation method according to claim 3, characterized in that: In the step A6, the defoaming agent is added after the coating has been initially cured, with a mixing speed of 50-100 rpm and a mixing time of 10-20 minutes.

10. The preparation method according to claim 3, characterized in that: During the preparation of the paint, quality inspection is carried out after each mixing step to ensure that the quality and proportion of each component meet the requirements. The final product must pass performance tests, including corrosion resistance tests, adhesion tests and weather resistance tests, to ensure that the performance of the paint meets the requirements for full sealing of the hull and external media.

Citation Information

Cited By

  • Corrosion-resistant environment-friendly coating as well as preparation method and application thereof

    CN120383864A